Computed Tomography of the Chest to Screen for Interstitial Lung Disease in Patients With Systemic Sclerosis at Expert Scleroderma Centers in the United States. Issue 7 (23rd April 2022) - Bernstein, Elana J.; Assassi, Shervin; Castelino, Flavia V.; Chung, Lorinda; Correia, Chase; Evnin, Luke B.; Frech, Tracy M.; Gordon, Jessica K.; Skaug, Brian A.; Hant, Faye N.; Hummers, Laura K.; Sandorfi, Nora; et al.
Abstract : Objective: Although a high‐resolution computed tomography (HRCT) scan of the chest is the gold standard test for the detection of interstitial lung disease (ILD), there is no consensus among rheumatologists regarding the use of HRCT to screen for ILD in their patients with systemic sclerosis (SSc). The aims of this study were to describe the HRCT ordering practices at SSc centers in the United States and to determine which patient characteristics are associated with HRCT performance. Methods: We performed a prospective cohort study of patients with SSc enrolled in the US‐based Collaborative National Quality and Efficacy Registry (CONQUER). We performed univariate logistic regression followed by multivariable logistic regression to determine which patient characteristics were associated with HRCT performance. Results: Of the 356 patients with SSc enrolled in CONQUER, 286 (80.3%) underwent HRCT at some point during their disease course. On multivariable analyses, missing total lung capacity percent predicted (odds ratio [OR] 3.26, 95% confidence interval [CI]: 1.53‐7.41, P = 0.007) was positively associated with ever having undergone HRCT, whereas a positive anti‐centromere antibody (OR 0.27, 95% CI: 0.12‐0.61, P = 0.008) and missing forced vital capacity percent predicted (OR 0.29, 95% CI: 0.10‐0.80, P = 0.005) were negatively associated with ever having undergone HRCT. There was a trend toward a positive association between crackles on pulmonary exam and ever having undergone HRCT (OR 2.28, 95% CI: 0.97‐6.05, P = 0.058), although this relationship did not reach statistical significance. Conclusion: The majority of patients with SSc enrolled in CONQUER underwent HRCT. A positive anti‐centromere antibody was the key clinical variable inversely associated with performance of HRCT.